Interkulturalitas, Hakikat Hidup dan Misi Kita: Menindaklanjuti ajakan Kapitel General 2012 - Sudhiarsa, Raymundus I Made (Perspektif, 2015)
The current article intends to discuss interculturality as the real condition where members of the Society of the Divine Word (SVD) carry out their mission ad extra as well as live out their lives ad intra in their religious communities. The tern interculturality is not really new for most of the members, since the rationale of the foundation of the Society in 1875 was exactly for cross-cultural mission, which means internationality or interculturality. The last General Chapter of the Society (2012) has just rediscovered interculturality as its heritage and mission commitment since the time of Saint Arnold Janssen, its founder. At the same time, interculturality was (and is) regarded as a particular gift of God to the Society. The article tries to put forward that it is very important for all the members to be competent in their intercultural life and mission. Training in intercultural competence, then, is a must in all levels of religious-missionary formation.